2005
DOI: 10.1124/jpet.105.093278
|View full text |Cite
|
Sign up to set email alerts
|

Oxymetazoline Inhibits Proinflammatory Reactions: Effect on Arachidonic Acid-Derived Metabolites

Abstract: The nasal decongestant oxymetazoline effectively reduces rhinitis symptoms. We hypothesized that oxymetazoline affects arachidonic acid-derived metabolites concerning inflammatory and oxidative stress-dependent reactions. The ability of oxymetazoline to model pro-and anti-inflammatory and oxidative stress responses was evaluated in cell-free systems, including 5-lipoxygenase (5-LO) as proinflammatory, 15-lipoxygenase (15-LO) as anti-inflammatory enzymes, and oxidation of methionine by agglomerates of ultrafine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
2
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(35 citation statements)
references
References 40 publications
1
31
2
1
Order By: Relevance
“…In addition to being an a-agonist, oxymetazoline has been shown to have various antioxidative and anti-inflammatory properties. [8][9][10][11][12] Whether any of these effects contributed to our results is unknown. The oxymetazoline was dosed once daily at night.…”
Section: Discussionmentioning
confidence: 55%
“…In addition to being an a-agonist, oxymetazoline has been shown to have various antioxidative and anti-inflammatory properties. [8][9][10][11][12] Whether any of these effects contributed to our results is unknown. The oxymetazoline was dosed once daily at night.…”
Section: Discussionmentioning
confidence: 55%
“…In upper respiratory tract infections, oxymetazoline and xylometazoline have been shown to inhibit neutrophilic phagocytosis and oxidative burst, resulting in a decrease in microbial killing, decreased generation of proinflammatory cytokines, and decreased inflammation. 16,17 Oxymetazoline has also recently been shown to have significant effects on the arachidonic acid cascade, strongly inhibiting 5-lipoxygenase activity and thus decreasing the synthesis of the highly proinflammatory leukotriene B 4 . 17 A potential clinical role for oxymetazoline, or other agents of this class, as inhibitors of inflammation and oxidative-stress dependent reactions in inflammatory and/or infectious skin conditions is intriguing but has yet to be investigated.…”
Section: 24-7mentioning
confidence: 99%
“…OXY has been demonstrated to have various antioxidant and anti-inflammatory properties in addition to its potent decongestive effect2425. Previous studies have demonstrated that the concomitant administration of MF and OXY may provide better improvements in AR patients, especially those with nasal congestion symptom262728293031.…”
Section: Discussionmentioning
confidence: 99%